Problematizando a indústria dos sonhos: questões sociológicas para analisar o cinema de entretenimento estadunidense - Túlio Cunha Rossi (Ciências Sociais Unisinos)
This paper discusses the importance of analysing Hollywood productions in Sociology. Most of these reflections derive from research for my PhD thesis, in which the use of movies to undertake consistent analyses of subjects relevant to life in society was central. Methodological questions about the analysis of fictional movies and its contributions to Sociology are dealt with, as well as about the presence of cinematographic references and audiovisual media in contemporary life. Thus, the article discusses how the mainstream cinema constitutes a relevant object of sociological analysis, which demands specific methods that are capable of going beyond the limits of technical analyses and a simple quantification of reception variables. At the same time, it also problematizes how this particular cinema affects social life and is affected by it.